Navigating the Future of Work: The Impact of AI on Organizational Trust - Barker, Kate (Digital Repository of Theses, 2024)
In the age of Generative Artificial Intelligence (GenAI), the traditional paradigms of trust in leadership are being profoundly challenged and reshaped. The rapid advancement of GenAI technologies offers unprecedented opportunities for innovation and efficiency but also poses significant risks related to misinformation, erosion of trust, and ethical dilemmas. This research paper delves into the complexities of maintaining and building trust in leadership amidst the proliferation of GenAI, aiming to uncover the challenges leaders face and strategize effective responses. The purpose of this study is to explore the impact of GenAI on the dynamics of trust in leadership, focusing on how the technology influences the spread of misinformation, the ethical considerations it entails, and the subsequent effects on organizational and societal trust. Through a comprehensive literature review, the paper identifies key areas where GenAI intersects with issues of trust and leadership, laying the groundwork for a deeper investigation. Methodologically, the study adopts an interdisciplinary approach, integrating insights from psychology, sociology, computer science, and organizational behavior. It employs a mixed-methods strategy, combining quantitative surveys with qualitative interviews and case studies to gather diverse perspectives from leaders across industries that have begun to integrate GenAI technologies. The research targets a range of organizations, from tech giants to traditional firms venturing into digital transformation, to provide a broad understanding of the challenges and strategies related to trust in the context of GenAI. Findings from the study highlight a nuanced landscape where GenAI acts as a double-edged sword in relation to trust. On one hand, GenAI can enhance decision-making processes, streamline operations, and personalize customer experiences, thereby potentially strengthening trust in leadership. On the other hand, the ability of GenAI to produce convincing yet fabricated content can undermine trust, as leaders grapple with the spread of misinformation and the ethical implications of AI-generated decisions. The conclusion of the research underscores the importance of adopting a balanced approach to leveraging GenAI in leadership practices. It calls for leaders to cultivate a deep understanding of the technology's capabilities and limitations, emphasizing the need for transparency, ethical responsibility, and ongoing dialogue with stakeholders to navigate the trust challenges posed by GenAI. The study proposes a framework for ethical AI governance and recommends strategies for leaders to foster an environment of trust, such as implementing robust verification processes for AI-generated content, promoting digital literacy, and engaging in ethical AI development and usage practices. This thesis contributes to the evolving discourse on trust in the age of GenAI, offering valuable insights for leaders seeking to harness the benefits of technological advancements while mitigating risks and preserving the foundation of trust that underpins effective leadership and organizational success.